A Novel Cogeneration System for the Simultaneous Production of Power and Cooling Operating with Geothermal Energy: A Case Study in La Primavera, Jalisco, México - Alejandro Pacheco-Reyes; Juliana Saucedo-Velázquez; Geydy Luz Gutiérrez-Urueta; Wilfrido Rivera (Resources)
More efficient systems and renewable energies are determinants of reducing the negative impact on the environment. A novel cogeneration system is modeled for the simultaneous production of power and cooling driven by geothermal energy utilizing an ammonia–water mixture. The system can be used in rural communities by using renewable energies or in industries where waste heat is available. The system is a modification of a Goswami cycle in which a separator has been added to produce an extra amount of ammonia vapor to increase the cooling effect. Energy and exergy analyses are conducted as a function of the main operating temperatures. From the optimization, it is found that the maximum energy utilization factor is 0.54, and the exergy efficiency is 0.37, producing 81.45 kW of power and 1068 kW of cooling. A case study is also conducted for a rural community located in the estate of Jalisco, México. The proposed system is capable of preserving 3750 L of milk/day while simultaneously producing 12.53 kW of power when 230.6 kW of geothermal energy is supplied at 120 °C.